Controlling Surface-plasmon-polariton Launching with Hot Spot Cylindrical Waves in a Metallic Slit Structure - Yao, Wenjie; Sun, Chengwei; Qihuang Gong; Chen, Jianjun (Nanotechnology, 2016)
Plasmonic nanostructures, which are used to generate surface plasmon polaritions (SPPs), always involve sharp corners where the charges can accumulate. This can result in strong localized electromagnetic fields at the metallic corners, forming the hot spots. The influence of the hot spots on the propagating SPPs are investigated theoretically and experimentally in a metallic slit structure. It is found that the electromagnetic fields radiated from the hot spots, termed as the hot spot cylindrical wave (HSCW), can greatly manipulate the SPP launching in the slit structure. The physical mechanism behind the manipulation of the SPP launching with the HSCW is explicated by a semi-analytic model. By using the HSCW, unidirectional SPP launching is experimentally realized in an ultra-small metallic step-slit structure. The HSCW bridges the localized surface plasmons and the propagating surface plasmons in an integrated platform and thus may pave a new route to the design of plasmonic devices and circuits.